(untitled) (Damascus University Journal for the economic and Political sciences, 2022)
This study aimed to test the impact of the spread of the Corona virus (Covid-19) on Damascus and Beirut exchange, for the period from 22 March 2020 for Damascus exchange, and from 21 April 2020 for Beirut exchange to 21 January 2021. The hypotheses were tested after choosing among several models according to the optimal model that uses stationary variables, and avoiding residuals’ serial correlation and heteroscedasticity problems. The results showed a negative, but not significant relation, between the number of new infections with (Covid-19) in Syria and the returns of Damascus Exchange Index, and trading volume. While, a positive and not significant relation appeared between the number of deaths announced due to (Covid-19) in Syria, and the returns of Damascus Exchange Index, and trading volume. The results also showed a positive but not significant relation between the number of new infections with (Covid-19) in Lebanon and the returns of Beirut Exchange Index, and trading volume. But the relation between the number of deaths announced due to (Covid-19) in Lebanon, and the returns of Beirut Exchange Index was negative and not significant. Whereas, it was positive and not significant between the number of deaths announced due to (Covid-19) in Lebanon and trading volume in Beirut exchange. The results also showed that using an improper statistical model would affect the results, as a relation appeared between the number of new infections with (Covid-19) in Syria and the returns of the Damascus Exchange Index and trading volume when using improper statistical model. This research recommends the need to increase investor awareness and activate electronic trading that can reduce the spread of (Covid-19).